Pengaruh Pendekatan Culturally Responsive Teaching (CRT) Terintegrasi Etnokimia dalam Meningkatkan Hasil Belajar Ranah Kognitif pada Materi Kimia Hijau di SMA/MA Kelas X - Laras Kusuma Wardani; Bakti Mulyani; Sri Retno Dwi Ariani; Sri Yamtinah; Mohammad Masykuri; Maria Ulfa; Ari Syahidul Shidiq (Jurnal Penelitian Pendidikan IPA, 2023)
Culture has an important role in realizing sustainable education. An Ethnochemistry-based Culturally Responsive Teaching Approach has the potential to integrate students' cultural and chemical concepts into classroom learning. However, this approach has not been widely implemented in schools. Therefore, this research aims to determine the effect of implementing an tthnochemistry-based culturally responsive teaching approach on improving cognitive learning outcomes in green chemistry material in high school. A quasi-experimental design involving 36 students in the experimental class and 36 students in the control class was used, utilizing a post-test with ten multiple choice questions to measure cognitive learning outcomes. The Kruskal-Wallis test was then applied to evaluate the effectiveness of the treatment. The research results show that the application of the Culturally Responsive Teaching approach which is integrated with ethnochemistry has an effect on increasing cognitive learning outcomes in green chemistry material.